Effects of the corona measures on the life of children and adolescents: Results of the German HBSC study 2022 - Franziska Reiß; Veronika Ottová-Jordan; Ludwig Bilz; Irene Moor; Kevin Dadaczynski; Ronja Maren Helmchen; Theresa Schierl; Saskia Sendatzki; Katharina Rathmann; Anne Kaman; HBSC Study Group Germany; Ulrike Ravens-Sieberer (Journal of Health Monitoring)
Background: The containment measures of the COVID-19 pandemic have changed many people’s daily lives. The study examines how children and adolescents assess the impact of the coronavirus measures on various areas of life. Methods: Overall, N = 6,475 students (11 – 15 years) in Germany took part in the representative ‘Health Behavior in School-aged Children (HBSC)’ study in 2022. Logistic regressions were performed to investigate the relationships between the perceived impact of the coronavirus measures on various areas of their lives by age, gender and family wealth. Results: Two years after the onset of the pandemic, children and adolescents reported both, positive and negative effects of the coronavirus measures. About a half of those surveyed perceived positive effects regarding social relationships. In contrast, approximately one in three respondents reported a deterioration in mental health and school performance. In particular, 11-year-olds, boys and wealthy students reported more often positive effects. Conclusions: The positive effects of the pandemic on the lives of children and adolescents in individual areas and the resilience (resistance) that is emerging here, as well as the results on more negative assessments of adolescents, girls and respondents with lower family wealth, can be used as a starting point for a needs-oriented and target group-specific health promotion in times of crisis. Future research should focus on the pandemic’s long-term effects on young people’s development.